Does economic upgrading lead to social upgrading in contact centers? Evidence from South Africa. Issue 3 (3rd July 2019) - Anwar, Mohammad Amir; Graham, Mark
ABSTRACT: Business process outsourcing (BPO) is seen by the South African government as key to employment generation. BPO operations are reasonably footloose and the industry's immense focus on workplace control and high levels of attrition means that the development potential of the BPO industry on workers in South Africa is a matter of critical concern. This article uses the global production network (GPN) framework to understand the developmental potentials of contact center jobs for workers in South Africa. The key argument is that economic upgrading among contact center firms can lead to both social upgrading and downgrading among workers.